How to Define Searching Sessions on Web Search Engines - Jansen, Bernard J.; Spink, Amanda; Kathuria, Vinish (Advances in Web Mining and Web Usage Analysis, 2007)
In this research, we investigate three techniques for defining user sessions on Web search engines. We analyze 2,465,145 interactions from 534,507 Web searchers. We compare three methods for defining sessions using: 1) Internet Protocol address and cookie; 2) Internet Protocol address, cookie, and a temporal limit on intra-session interactions; and 3) Internet Protocol address, cookie, and query reformulation patterns. Research results shows that defining sessions by query reformulation provides the best measure of session identification, with a nearly 95% accuracy. This method also results in an 82% increase in the number of sessions compared to Internet Protocol address and cookie alone. Regardless of the method, mean session length was fewer than three queries and the mean session duration was less than 30 minutes. Implications are that unique sessions may be a better indicator than the common industry metric of unique visitors for measuring search traffic. Results of this research may lead to tools to better support Web searching.